“The borrow”: Kafkaesque challenges for the phenomenology of inhabiting - Rubio, Roberto (Itinerari, 2024)
Dwelling is one of the main human experiences. According to phenomenology, the relevance of such an experience consists in the fact that it intersubjectively configures one’s own world as a home world (Heimwelt) and distinguishes it from the alien world (Fremdwelt). To dwell is to build the home as such. Home building, for its part, has been considered phenomenologically from two opposing possibilities: on the one hand, calculating thinking and the uncritical realization of technical potentialities; on the other hand, a meditative thinking, characterized by the depowering of the calculating reason and the orientation towards a poetic way of dwelling. Now, a particularly influential description of home building is offered by Kafka’s text posthumously entitled “Der Bau”, which was diversely entitled in Spanish: la construcción (the building), la obra (the work), la guarida (the burrow), la madriguera (the den). In the present paper, I will try to contrast Kafka’s description with the phenomenological approach to dwelling, considered especially regarding Husserl and Heidegger. I will carry out this contrast in two steps: first, I will highlight descriptions contained in Kafka’s tale that call into question central propositions and premises of the phenomenological approach. Second, I will outline possible lines of response, from phenomenology to Kafka’s challenges.